The representation of likeability in American pop culture: A case study of Clueless (1995) - Prasetyo, Nikken; Muna, Nailil (Accentia: Journal of English Language and Education, 2025)
Teenage popularity is often portrayed negatively in American pop culture, frequently associated with bullying, beauty privilege, and social exclusion. This study offers an alternative perspective by applying Mitch Prinstein’s theory of likeability, which frames popularity as an indicator of strong interpersonal relationships and high social acceptance. This perspective is captured in Amy Heckerling’s Clueless (1995), particularly its depiction of the "popular girl" trope as shaped by fashion, social status, and influence among affluent Beverly Hills teens. Focusing on the film’s leading character, Cher Horowitz, this study examines how likability is represented as a positive form of popularity. This study employed a descriptive method to analyze how Cher’s character embodies likeability as a form of social acceptance. The primary data consisted of the film script, including dialogue, narration, and monologue, while secondary sources included books, journals, and scholarly articles. Data collection involved watching the film, reading the script, and systematically identifying relevant elements. Data were analyzed using an interpretive approach to unpack and discover the underlying themes, patterns, and messages conveyed in the narrative. Findings reveal that Cher’s popularity aligns with the likability type, characterized by her ability to make others feel happy, appreciated, and included. The portrayal of such key traits offers a contrast to more negative portrayals of popularity found in other American teen movies, such as Cruel Intentions (1999) and Mean Girls (2004).